Investigation of the embedded fìber bragg grating temperature sensor - Tam, Tran Thi; Trung, Dang Quoc; Vu, Tran Anh; Minh, Le Huu; Chung, Do Ngoc (VNU Journal of Science: Mathematics - Physics, 2007)
Abstract: